ANALISIS MENGENAI NASAB DAN HAK WARIS ANAK HASIL PERKAWINAN BAWAH TANGAN (ANAK LUAR KAWIN) MENURUT HUKUM ISLAM - , Noor Arini Haq, Rosikhoh Umdatul Ulya (Fakultas Hukum Universitas Sebelas Maret, 2014)
Abstract Islamic law had different views with positive law in terms of the definition lawful marriage. In islamic law, marriage said to be valid if has qualified and made it so pillars, so there are no additional terms as set forth in positive law (Act No. 1 of 1974 about marriage), as the marriage valid if the set that has been noted to the Institution of marriage Registrar. Difference in this view then impacted the setting will be the ânasabâ (relationship) to the mating with her parents, and heir on the rights of the child marriage. Islamic law stipulates that children outside of marriage not only has ânasabâ by her mother and her mothers family. The child is also not entitled to obtain the right heir of his father. Nevertheless, based on the ruling of the Constitutional Court No. 46/PUU-VIII/2010 children outside marriage can still obtain his rights along can be proven through medical and medical apparatus that dad in question is indeed his biological father realilty is. Keywords : Forbidden, children outside of marriage, inheritan